AGRICULTURAL EDUCATION MOVE IN THE ABDULHAMID II PERIOD: HUDAVENDIGAR HAMIDIYE AGRICULTURAL PRACTICE SCHOOL AND SAMPLE FARM (1891-1909) - (:unkn) unknown (SELCUK UNIV, INST TURKISH STUDIES, 2021)
During the reign of Abdulhamid II, there have been many developments to modernize education. As in primary, secondary, and higher education, new educational institutions were established in the field of vocational and technical education. Especially in vocational education, the socio-economic situation of the country is taken into consideration and steps have been taken. One of the most basic examples in this regard is the question of agriculture and agricultural schools. After Abdulhamid II came to power, modernization, and agriculture education in the field of agriculture came to the agenda and a long-lasting first step was taken by entering an agricultural school facility in Halkali. Agricultural Schools were not only limited to Istanbul, but also established in provinces. In this study, Hudavendigar Agricultural School and Sample Farm opened in Bursa in line with the educational policies and agriculture understanding of the period of Abdulhamid II was discussed. In this context, detailed information about the opening process of the school, administrative and teaching staff, curriculum and courses, examinations, number of students, graduation, social status of the school and the farm were given. The Agricultural School in Bursa, along with the Halkali and Selanik Agricultural Schools, was one of the three educational institutions in the Ottoman Empire where modern agriculture education was given. Subsequently, these schools continue to exist in the Constitutional Monarchy and the Republic of Turkey, the only school of its kind today maintained its historic mission of the agricultural school built Abdulhamid II period, has a unique place in the history of Turkish education.
Keywords: Abdulhamid II; Bursa; Agriculture; Modern Education; Agricultural Education; Agriculture School